Characterizing changes in obsessive–compulsive symptoms over the course of treatment for adolescent bulimia nervosa. Issue 10 (21st July 2022) - Reilly, Erin E.; Gorrell, Sasha; Brosof, Leigh; Lock, James; Le Grange, Daniel
Abstract: Objective: Data suggest that obsessive–compulsive (OC) symptoms are commonly observed in adolescents with eating disorders and predict poorer treatment response. Further, emerging data among adults suggest that changes in OC symptoms relate to changes in eating disorder symptoms across treatment. Given evidence that early invention decreases risk for protracted illness, evaluating processes that may relate to treatment response will be useful in increasing the effectiveness of existing interventions. Therefore, the current investigation explored changes in general and eating disorder‐specific OC symptoms throughout family‐based treatment (FBT) and cognitive behavioral therapy (CBT) for bulimia nervosa (BN), as well as associations among these changes and eating disorder outcomes at follow‐up. Method: Participants ( N  = 110) received 18 sessions of FBT or CBT and completed measurements of general and eating disorder‐specific OC symptoms at baseline, end‐of‐treatment, and 6‐ and 12‐month follow‐up. Results: Multilevel models indicated that across both treatments, there was no change in general OC symptoms, whereas all eating disorder‐related OC symptoms decreased over treatment and follow‐up. Exploratory analyses indicated that lower severity in discharge eating‐disorder‐specific OC symptoms contributed to lower eating pathology at follow‐up. Discussion: Together, findings support the efficacy of both FBT and CBT in helping to reduce eating disorder‐specific OC symptoms and suggest that adjunctive intervention may be required for ameliorating general OC symptoms in this population. Public significance: BN is associated with significant increases in mortality and societal cost, and there is a pressing need for innovations within available treatments for young people with this disorder. In the current study, we explore the extent to which existing evidence‐based treatments for adolescent BN are effective in targeting obsessive–compulsive symptoms, a known predictor of treatment response and common co‐morbidity in this population.